Respuesta :

Answer:

x = -5

y = 4

Step-by-step explanation:

3x + 4y = 1    /*(-4)

4x + 5y = 0   /*3

---------------------

-12x - 16y = -4

12x + 15y = 0     +

---------------------

-y = -4

y = 4

---------------------

12x = -15y

12x = -60

x = -5

---------------------

Answer: x = - 5

y = 4

Step-by-step explanation:

The given system of linear equations is expressed as

3x + 4y = 1- - - - - - - - - - - - -1

4x + 5y = 0- - - - - - - - - - - -2

We would eliminate x by multiplying equation 1 by 4 and equation 2 by 3. It becomes

12x + 16y = 4- - - - - - - - - - -3

12x + 15y = 0- - - - - - - - - - - -4

Subtracting equation 4 from equation 3, it becomes

y = 4

Substituting y = 4 into equation 1, it becomes

3x + 4 × 4 = 1

3x + 16 = 1

Subtracting 16 from the left hand side and the right hand side of the equation, it becomes

3x + 16 - 16 = 1 - 16

3x = - 15

Dividing the left hand side and the right hand side of the equation by 3, it becomes

3x/3 = - 15/3

x = - 5